Structural capacity and continuum of snakebite care in the primary health care system in India: a cross-sectional assessment - Bhaumik, Soumyadeep; Norton, Robyn; Jagnoor, Jagnoor (BMC family practice, 2023)
Background In 2019, the World Health Organization, set a target to halve the burden of snakebite, by 2030, and identified ‘health systems strengthening’ as a key pillar of action. In India, the country with most snakebite deaths, the Union Government identified (in September 2022) training of health workers as a priority action area. In this policy context, we provide empirical evidence by analysing the most recent nationwide survey data (District Level Household and Facility Survey − 4), to assess structural capacity and continuum of snakebite care in primary health care system in India. Methodology We evaluated structural capacity for snakebite care under six domains: medicines, equipment, infrastructure, human resources, governance and finance, and health management information systems (HMIS). We categorised states (aspirant, performer, front-runner, achiever) based on the proportion of primary health centres (PHC) and community health centres (CHC), attaining highest possible domain score. We assessed continuum of snakebite care, district-wise, under five domains (connectivity to PHC, structural capacity of PHC, referral from PHC to higher facility, structural capacity of CHC, referral from CHC to higher facility) as adequate or not. Results No state excelled ( front-runner or achiever) in all six domains of structural capacity in PHCs or CHCs. The broader domains (physical infrastructure, human resources for health, HMIS) were weaker compared to snakebite care medicines in most states/UTs, at both PHC and CHC levels. CHCs faced greater concerns regarding human resources and equipment availability than PHCs in many states. Among PHCs, physical infrastructure and HMIS were aspirational in all 29 assessed states, while medicines, equipment, human resources, and governance and finance were aspirational in 8 (27.6%), 2 (6.9%), 17 (58.6%), and 12 (41.4%) states respectively. For CHCs, physical infrastructure was aspirational in all 30 assessed states/UTs, whereas HMIS, medicines, equipment, human resources, and governance and finance were aspirational in 29 (96.7%), 11 (36.7%), 27 (90%), 26 (86.7%), and 3 (10%) states respectively. No district had adequate continuum of snakebite care in all domains. Except for transport availability from CHC to higher facilities (48% of districts adequate) and transport availability from PHC to higher facilities (11% of districts adequate), fewer than 2% of districts were adequate in all other domains. Conclusion Comprehensive strengthening of primary health care, across all domains, and throughout the continuum of care, instead of a piece-meal approach towards health systems strengthening, is necessitated to reduce snakebite burden in India, and possibly other high-burden nations with weak health systems. Health facility surveys are necessitated for this purpose.